The Public's Influence on the U.S. District Courts in Discrimination Cases. (19th April 2022) - Rivero, Albert H.
Abstract: Do judges follow public opinion when they decide cases that present related issues over which the public has differing ideological views? This study addresses this question by comparing the U.S. District Court behavior in race and gender discrimination cases. By measuring public opinion on two issue areas that raise similar legal questions, I provide a better estimate of the effect of public opinion with fewer confounding variables relating to the agenda of the federal courts. Using a difference-in-differences approach, I show that district court judges are more likely to vote liberally in gender discrimination cases than in race discrimination cases when public opinion on gender becomes relatively more liberal than public opinion on race. This holds even when including a series of important covariates such as demographic information about the judges. This paper thus provides further support for a counterintuitive claim in the literature: unelected judges may nonetheless respond to public opinion.